Husband Participation in Pregnant Women's Classes on Decision Making in P4K (Delivery Planning and Complication Prevention Program) - Anwar, Khalidatul Khair; Nasrawati; Yustiari; Jumrah; Anwar, Miftahtul Khair (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
The maternal mortality rate reaches 305 per 100.000 live births, where 76% of maternal deaths occur in the labor and postpartum phases. The high mortality of maternity mothers is caused by delays in family decisions in handling complications. Delays in getting help are caused by the patient's condition, which is already very severe until the place of referral due to the postponement of the family in making a decision to be referred immediately. The Childbirth Planning and Complication Prevention (P4K) program in the pregnant women's class is an activity facilitated by midwives in the village to increase the active role of husbands, families, and communities in planning safe childbirth and preparing for complications for pregnant women. The study aims to determine the effect of the husband's participation in the pregnant women's class on P4K clinical decision-making. This type of research is observational analytics. The study was carried out in the Working Area of the Soropia Health Center. The total sample was 46 husbands who had pregnant wives, consisting of 23 husbands who participated in the pregnant women's class and 23 husbands who did not participate in the pregnant women's class. The data were analyzed using a chi-square test with the SPSS application. This study shows that, on average, husbands who participate in the course of pregnant women making decisions are in the excellent category. The decision-making in question is preparing for childbirth and preventing complications. The chi-square test results show a value of p=0.000 <α. The husband's participation in the pregnant women's class influences P4K decision-making. Based on this, health workers need to socialize continuously with their husbands about the importance of attending classes for pregnant women so that they can provide knowledge about childbirth preparation and the prevention of complications.